Distinct Molecular Phenotypes of Direct vs Indirect ARDS in Single-Center and Multicenter Studies - Calfee, Carolyn S. (Chest, 2015)
BACKGROUND: ARDS is a heterogeneous syndrome that encompasses lung injury from both direct and indirect sources. Direct ARDS (pneumonia, aspiration) has been hypothesized to cause more severe lung epithelial injury than indirect ARDS (eg, nonpulmonary sepsis); however, this hypothesis has not been well studied in humans. METHODS: We measured plasma biomarkers of lung epithelial and endothelial injury and inflammation in a single-center study of 100 patients with ARDS and severe sepsis and in a secondary analysis of 853 patients with ARDS drawn from a multicenter randomized controlled trial. Biomarker levels in patients with direct vs indirect ARDS were compared in both cohorts. RESULTS: In both studies, patients with direct ARDS had significantly higher levels of a biomarker of lung epithelial injury (surfactant protein D) and significantly lower levels of a biomarker of endothelial injury (angiopoietin-2) than those with indirect ARDS. These associations were robust to adjustment for severity of illness and ARDS severity. In the multicenter study, patients with direct ARDS also had lower levels of von Willebrand factor antigen and IL-6 and IL-8, markers of endothelial injury and inflammation, respectively. The prognostic value of the biomarkers was similar in direct and indirect ARDS. CONCLUSIONS: Direct lung injury in humans is characterized by a molecular phenotype consistent with more severe lung epithelial injury and less severe endothelial injury. The opposite pattern was identified in indirect lung injury. Clinical trials of novel therapies targeted specifically at the lung epithelium or endothelium may benefit from preferentially enrolling patients with direct and indirect ARDS, respectively.